Empowering Disabled MSMEs through Technology Adaptation and Digital Marketing in Productivity Turnover - Dian Prianka; Ardeliah Tjiptawan; Adhika Putra Wicaksana (GUYUB: Journal of Community Engagement, 2026)
Devan Bamboo, an MSME owned by an entrepreneur with a disability, faced a productivity–revenue paradox: a 170% increase in productivity was followed by a 26% decline in revenue. This occurred due to a mismatch between production output and market demand, limited access to wider markets, and the inability to produce high-value customized products using manual methods, alongside weak digital marketing. This community engagement program implemented an integrated empowerment model using Rapid Rural Appraisal (RRA) and Asset-Based Community Development (ABCD). RRA was used to identify operational bottlenecks, while ABCD guided solution design by leveraging the partner’s existing creative strengths. The intervention included disability-adapted production technologies (bamboo cutting, splitting, and laser cutter machines adjusted for wheelchair use) and intensive digital marketing training (e-commerce, CorelDRAW, and Instagram strategy). The results showed significant improvements. Production efficiency increased, with over 50% of products adopting laser-cut designs. Digital performance rose sharply (Instagram reach +244%). Importantly, revenue trends recovered, with omzet increasing in Quarter III after previous decline. This study concludes that integrating adaptive technology and digital skills effectively aligns productivity with market demand, providing a sustainable empowerment model for disability-owned MSMEs.